The Application of Lean Management Tools in Management of Sustainable Development of the Enterprise - MaÅ‚gorzata ÅÄ™gowik-MaÅ‚olepsza (International Journal of Supply Chain Management, 2019)
In the paper, the concept of sustainable development in relation to enterprise management as well as the idea of sustainable enterprise against the background of the concept of sustainable development have been presented. In the subsequent part of the study, the selected tools of the lean management concept have been depicted. In the last part, the efficiency of the implementation of lean management tools in the context of the implementation of assumptions of sustainable development has been assessed. In the paper, the following research question has been formulated: how does the implementation of lean management tools in the enterprise translate into the efficiency of the implementation of assumptions of sustainable development? On the other hand, the objective of the study has been to assess the efficiency of the implementation of lean management tools in reduction in operating costs and to analyze the effects of this implementation on the implementation of assumptions of sustainable development. In order to achieve the objective of the study, the relationship between the level of costs of the implementation of lean management tools and the costs of the implementation of assumptions of sustainable development has been analyzed, which has indicated the impact of an increase in the listed costs on an increase in return on sales in years 2009-2017. The research clearly shows that continuous improvement in the implementation of activities and processes, including the implementation of assumptions of sustainable development allows for achieving success in the analyzed area. The applied research methods are: literature studies, case study, trend analysis of the costs of the implementation of lean management tools.